First record of an epibiont protozoan Epistylis sp (Ciliophora, Peritrichia) attached to Ergasilus chelangulatus (Ergasilidae) in Brazil - Azevedo, Rodney Kozlowiski [UNESP] (2014)
In the present paper, we described the first record of an epibiont protozoan Epistylis sp. Ehrenberg, 1830 (Ciliophora, Peritrichia) attached to Ergasilus chelangulatus Thatcher and Brasil-Sato, 2008, parasite of Pimelodus maculatus Lacepede, 1803 in Brazil, with electron microscope observations. Fish were collected in Veados River, state of Sao Paulo and the crustacean Ergasilus chelangulatus being registered for the first time in this river, expanding its geographical distribution in Brazil.